Optimizing packet size in post-quantum NB-IoT systems: Signature aggregation and Merkle tree pruning approaches - Do, Thi Bac; Dinh, Khanh Linh (Journal of Computer Science and Cybernetics, 2025)
With the increasing adoption of post-quantum cryptographic schemes such as SPHINCS+ in Narrowband IoT (NB-IoT) systems, a major challenge arises from large packet size overhead - often reaching approximate 34 KB per transmission due to stateless hash-based signature metadata. This paper investigates practical techniques for reducing this overhead while maintaining quantum resilience, including signature aggregation across multiple devices, Merkle tree pruning within SPHINCS+, and selective signing policies based on session frequency. We implement these strategies on an ESP32-WROOM-32 microcontroller interfaced with a SIM7080 NB-IoT module, demonstrating that packet size can be reduced by up to 60% through intelligent session management and optimized scheduling. Our results provide actionable insights for system architects aiming to deploy post-quantum security within strict bandwidth constraints typical of LPWAN environments.